Rozwiązane

Wyrażenie doprowadź do najprostszej postaci :
a) ( 3pkt) 2a( 3b− 4a ) − 3b(a- 2b)=

b) (2pkt) ( 2x - y)(4y - 5x)=

c)(3pkt) (3x-1)(5-2x)(3x+2)=

d)( 4pkt) -2( 3x-6a) - ( - a +4x) + (- 8x +a)=



Odpowiedź :

Odpowiedź:

a) 3ab - 4a2 - 6b2

b) 13y - 10x2 -4y2

c) 39x2 - 18x3 - 19x - 10

d)  -18x + 14a

Szczegółowe wyjaśnienie:

a) 2a(3 b - 4a) - 3b(a-2b) = 6ab - 4a2 - 3ab - 6b2 = 3ab - 4a2 - 6b2

b) (2x - y)(4y -5x) = 8xy - 10x2 - 4y2 + 5xy = 13y - 10x2 -4y2

c) (3x-1)(5-2x)(3x+2) = (15x - 6x2 - 5 + 2x)(3x+2) =(17x - 6x2 - 5)(3x+2) = 51x2 - 18x3 - 15x + 34x - 12x2 - 10 = 39x2 - 18x3 - 19x - 10

d) -2(3x-6a) - (-a+4x) + (-8x+a) = -6x + 12a + a - 4x - 8x +a = -6x - 4x - 8x + 6a + a +a = -18x + 14a